A COMPARISON BETWEEN STAD-TYPE AND TPS-TYPE COOPERATIVE LEARNING IN MIDDLE SCHOOL STUDENTS' GEOMETRY LEARNING - Asri Ode Samura (IKIP Siliwangi and I-MES, 2018)
This study aims to describe and compare the effectiveness of the application of STAD and TPS types in cooperative learning to the students. This study was a quasi-experiments research in which students were designed into a form of the experimental group (pre-test and post-test group designs), where the cooperative learning of STAD and TPS types will be applied in learning mathematics. The population in this study were junior high school students in Ternate, while samples were taken by 60 random students who had the same characteristics as the population. The result of the study shows that cooperative learning model of both STAD and TPS types are very effective to be applied on studying mathematics. However, between the STAD and TPS types of cooperative learning, the STAD types are more effective than TPS, seen from accomplishing standards of competence, mathematical communication skills, and mathematical thinking ability of Junior High School students.